(untitled) (Modern education and development, 2025)
This paper explores the fundamental linguistic phenomenon of antonymy, examining how words develop opposite meanings and function within language systems. We analyze various types of antonym relationships, their cognitive processing, and their role in structuring semantic fields. Drawing on examples from multiple languages, the study highlights the complex nature of word oppositions and their importance in communication, lexicography, and language acquisition.